Influence of Leadership, HR Quality, and Regulation Implementation on Corruption in Government Procurement - Lijan Poltak Sinambela; Siddig Alamsyah; Muhammad Teguh Herwidiyanto (International Forum of Researchers and Lecturers, 2025)
Corruption is an extraordinary crime that damages the foundation of the state. In the context of Government Procurement of Goods/Services (PBJP), corrupt behavior still occurs even though it has been regulated through Presidential Regulation Number 12 of 2021 as an amendment to Presidential Regulation Number 16 of 2018. The implementation of the PBJP policy is considered to be not able to effectively suppress the potential for corruption, so other variables are needed that affect the effectiveness of the policy. This study aims to analyze the direct and indirect influence of the leadership style and quality of human resources (HR) of the state civil apparatus on the potential for corruption through the implementation of PBJP policies. The research method used is quantitative with the Partial Least Squares - Structural Equation Modelling (PLS-SEM) approach, which aims to test the relationship between latent variables and confirm the influence of leadership style and quality of human resources on potential corruption through the effectiveness of PBJP implementation. The research population includes elements of PBJP policy implementation within the Corruption Eradication Commission (KPK), including PPK, procurement officials, UKPBJ working groups, and goods/service providers. The sample was determined by purposive random sampling, consisting of internal and external implementers of PBJP at the KPK with a budget value of more than IDR 1 billion in the 2024 fiscal year. The results of the study show that leadership style has a positive effect on the implementation of PBJP and directly reduces the potential for corruption. The quality of ASN human resources has a positive effect on the implementation of PBJP, but it has a double effect on the potential for corruption. The mediation test showed that the implementation of PBJP mediated part of the influence of leadership style and human resource quality on potential corruption, with the direction of influence changing from positive to negative. These findings confirm the importance of the effectiveness of the implementation of PBJP policies in suppressing the potential for corruption within the KPK.